2005
DOI: 10.1093/ajcn/82.5.1082
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness of early screening and treatment of malnourished patients

Abstract: Screening with the SNAQ and early standardized nutritional care improves the recognition of malnourished patients and provides the opportunity to start treatment at an early stage of hospitalization. The additional costs of early nutritional care are low, especially in frail malnourished patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
199
2
31

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(235 citation statements)
references
References 15 publications
3
199
2
31
Order By: Relevance
“…Along with this, it has been demonstrated that early screening and intervention allow reducing the LOS of at least 1 day per patient (Kruizenga et al, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…Along with this, it has been demonstrated that early screening and intervention allow reducing the LOS of at least 1 day per patient (Kruizenga et al, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…Early identification of subjects at risk of malnutrition and those who are already undernourished in different healthcare settings, together with their nutritional management, is essential to be able to minimise the deleterious effects of malnutrition and its negative impact on healthcare spending and the sustainability of the system (17)(18)(19). The European Society for Clinical Nutrition and Metabolism (ESPEN) recommends the Mini Nutritional Assessment (MNA) as the screening (MNA-screening) and assessment (MNA-assessment) instrument in patients over the age of 65 years (20).…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…Nutritional intervention (dietary counselling, oral nutritional supplements, enteral nutrition and parenteral nutrition) has a positive effect on outcome (Odelli et al, 2005;O'Flynn et al, 2005;Stanga et al, 2007) by reducing complication rates, LOS and costs of admission (Elia et al, 2005;Kruizenga et al, 2005).…”
Section: Introductionmentioning
confidence: 99%